New Insight into the Structure, Development, Functions and Popular Disorders of Bursa Fabricii. (26th February 2013) - Madej, J. P.; Chrząstek, K.; Piasecki, T.; Wieliczko, A.
Summary: Humoral immune responses in birds, contrary to mammals, depend on the normal functioning of bursa Fabricii. Recent studies have delivered new information about the structure, development and origin of cells that compose the bursa environment. Several viral infections affect bursa, causing lymphocyte depletion or excessive proliferation. This review summarizes data on the development and histology of healthy bursa and introduces some common disorders that affect this organ.